Parasitism Potential of Egg Parasitoid, Trichogramma chilonis against Spodoptera frugiperda on Maize - Ishtiaq, Muhammad; Jahangir, Shoaib; Sharif, Umer; Faheem, Umair; Shahid, Muhammad Rafiq; Ahmad, Naeem (Journal of Agriculture and Biology, 2025)
The fall armyworm (FAW), Spodoptera frugiperda, is highly destructive polyphagous and invasive insect pest of maize, causing considerable yield losses and is becoming increasingly difficult to manage due to over-reliance on chemical insecticides and the development of resistance. Egg parasitoids such as Trichogramma chilonis offer a promising approach for the biological control of this pest through sustainable integrated pest management (IPM). Although Trichogramma spp. are recognized as effective parasitoids of lepidopteran pests, there is limited local data on their efficacy, host preference, age-specific performance, and field application of T. chilonis against S. frugiperda on maize under Pakistani conditions. In this study, both laboratory and field experiments were conducted to evaluate the efficacy of T. chilonis against FAW. Laboratory tests assessed parasitism and emergence at different of FAW eggs (20-100 eggs), host preference between S. frugiperda and Sitotroga cerealella, the effect of parasitoid female age (24 h vs. 48 h), and the influence of host egg age. Field trials compared different frequencies and numbers of Trichogramma card applications in maize plots. Results indicated that parasitism rates increased with egg density with a maximum parasitism of 46.1 observed at 100 eggs per female. T. chilonis exhibited a preference for S. cerealella eggs over FAW eggs and demonstrated higher parasitism on fresh FAW eggs compared to older eggs, while 48-hour-old female parasitoids outperformed 24-hour-old females. In field trials, deploying two Trichogramma cards per week resulted in the greatest reduction in FAW larval populations and the least amount of plant damage. These findings highlight that T. chilonis is a promising biocontrol agent against FAW and can be effectively integrated into IPM programs through frequent releases of Trichogramma cards.
Keywords: Biological control; Integrated pest management; Egg parasitism; Host preference